Contrast Enhancement of Brain Aneurysms on High-Resolution Vessel Wall Imaging [HR-VWI] Correlates with the Presence of Microbleeds - Roa, Jorge A; Zanaty, Mario; Piscopo, Anthony J; Morris, Timothy W; Sabotin, Ryan; Ishii, Daizo; Varon, Alberto; Raghuram, Ashrita; Lu, Yongjun; Samaniego, Edgar A; Hasan, David M (Cardiology and Cardiovascular Medicine, 2021)
Background: Wall enhancement of unruptured intracranial aneurysms (UIAs) on high-resolution vessel wall imaging (HR-VWI) has been applied as a surrogate of inflammation. MR-quantitative susceptibility mapping (QSM) can identify microbleeds (MBs) at the interface between aneurysm wall and brain tissue preceding subarachnoid hemorrhage. Objective: To assess the correlation between HR-VWI and QSM findings and define an optimal cut-off for aneurysm wall enhancement based on the presence of MBs. Methods: Patients with UIAs prospectively underwent QSM and HR-VWI. UIAs were deemed unstable when MBs were identified on QSM. The contrast enhancement ratio between maximal signal intensity values measured in the aneurysmal wall and the pituitary stalk (CRstalk) on T1 post-contrast images was calculated. Multiple t-tests were computed to assess the correlation between morphological variables, PHASES scores, CRstalk, and presence of MBs. A ROC curve was plotted to determine the best CRstalk cutoff to differentiate stable from unstable UIAs. Results: A total of 81 UIAs were analyzed: 71 stable (MBs absent) and 10 unstable (MBs present). Unstable UIAs were larger (8.4 ± 5.5 mm vs 5.5 ± 2.3 mm, P=0.007), showed higher CRstalk (0.6 ± 0.2 vs 0.5 ± 0.1, P=0.05), and scored higher on PHASES (6.9 ± 3.5 vs 4.8 ± 2.6, P=0.02). ROC curve analysis demonstrated the best CRstalk cut-off to discriminate between UIAs with and without MBs was ≥ 0.55 (82% sensitivity, 67% specificity). Conclusion: There is a strong positive association between aneurysmal wall enhancement and presence of MBs. CRstalk ≥ 0.55 may be used as a surrogate biomarker of aneurysmal instability in clinical practice.